Study of characteristics of the supraglacial runoff of the Austre Grønfjordbreen, Spitsbergen - R. A. Chernov (Лëд и снег)
Surface runoff on the glacier is represented by two aquifers: a hydro-network of streams and a porous layer of melting crust in which meltwater moves. The first one transfers water from the snowmelt zone, and the second one drains the ablation area. Data on the state of the melting crust at various levels of the glacier and the speed of water movement in it had been obtained. The water store in the melting crust were estimated, the effect of daily ablation on the runoff in the pores and micro-streams was shown. With a limited water supply in the melting crust, the increase in runoff takes place due to the formation of micro-streams having no channels. As the distance from the snow line increases and the ablation becomes more intensive, the portion of streams becomes greater. Observations on the glacier made at different levels showed a qualitative agreement with our estimates. As for the hydro-network, water discharges in watercourses of various sizes and the rate of water transit in them were estimated. It is shown that the meandering of the channels results in regulation of the rate of water transit. For small streams with water flow rate smaller than 200 l/s, this speed turned out to be 0.98 ± 0.25 m/s, for larger streams it was equal to 1.20 ± 0.11 m/s. Calculations of snow and ice melt based on the air temperature above the glacier made possible to estimate the channel runoff in both, the hydro-network, and the weathering crust. During the period of active snowmelt, when the snow line moves lower, the main contribution to the surface runoff is made by the hydro-network of watercourses. As the snow line rises and the area of open ice increases, the share of runoff in the weathering crust increases. By the end of the summer period, runoff in the weathering crust becomes predominant.